Decentralized water collection systems for households and communities: Household preferences in Atlanta and Boston. (15th December 2019) - Lu, Zhongming; Mo, Weiwei; Dilkina, Bistra; Gardner, Kevin; Stang, Shannon; Huang, Ju-Chin; Foreman, Maria Christina
Abstract: Development of sustainable and resilient water infrastructure is an urgent challenge for urban areas to secure long-term water availability and mitigate negative impacts of water consumption and urban development. A hybrid system that combines centralized water infrastructure and household decentralized water facilities, including rainwater harvesting and greywater recycling, may be a solution to more sustainable and resilient water management in urban areas. Understanding household and community preferences for decentralized water facilities is important to inform the design and ultimately the promotion and adoption of such systems. In this study, we conducted a discrete choice experiment, via Amazon Mechanical Turk, to collect data on household choices of different decentralized water facility designs in two U.S. cities, Atlanta, Georgia and Boston, Massachusetts. Based on the responses to the choice experiment, we then developed a latent-class choice model to predict households' preferences of decentralized system design features and examine the influence of socioeconomic and personal characteristics on heterogeneous class membership. We identified six major classes of preferences in Atlanta and Boston, respectively, and evaluated how readily each class is likely to choose a decentralized water facility. Atlanta and Boston have some classes sharing similar preferences for decentralized water systems, but the socioeconomic and personal characteristics of these classes in the two cities are different. We found that the early adoption of decentralized water facilities is positively related to neighbors' adoptions and pressure of water scarcity increases households' willingness to share a decentralized facility. The visualization of spatial distribution of the classes highlighted early demand of decentralized water facilities is likely to emerge in low-property-value communities, which creates a unique opportunity for introducing decentralized water facilities during water infrastructure renovations. Our study provides a framework through citizen engagement to understand social demand and to inform the promotion of decentralized water facilities. Graphical abstract: Image 1 Highlights: A choice experiment on decentralized water systems was conducted in two US cities. Six unique social classes were identified in each city using latent-class analysis. Notable preference heterogeneity among residents was found in both cities. Neighbors' choice and perception of water scarcity influence class memberships. Downtown Atlanta and southeastern Boston have higher proportions of quick adopters.